Billy Waters is Dancing Or, How a Black Sailor Found Fame in Regency Britain - Shannon, Mary L. (Yale University Press, 2024)
The story of William Waters, Black street performer in Regency London, and how his huge celebrity took on a life of its own Every child in Regency London knew Billy Waters, the celebrated "King of the Beggars." Likely born into enslavement in 1770s New York, he became a Royal Navy sailor. After losing his leg in a fall from the rigging, the talented and irrepressible Waters became London's most famous street performer. His extravagantly costumed image blazed across the stage and in print to an unprecedented degree. For all his contemporary renown, Waters died destitute in 1823-but his legend would live on for decades. Mary L. Shannon's biography draws together surviving traces of Waters' life to bring us closer to the historical figure underlying them. Considering Waters' influence on the London stage and his echoing resonances in visual art, and writing by Douglass, Dickens, and Thackeray, Shannon asks us to reconsider Black presences in nineteenth-century popular culture. This is a vital attempt to recover a life from historical obscurity-and a fascinating account of what it meant to find fame in the Regency metropolis